Energy Performance Evaluation and Economic Analysis of Insulation Materials of Office Building in Korea - Choi, Bo Eun; Shin, Ji Hyun; Lee, Jin Hyun; Kim, Hyo Jun; Kim, Sun Sook; Cho, Young Hum (Advances in Civil Engineering, 2018)
Building energy conservation measure (ECM) of insulation materials suitable for the domestic situation in the construction sector (passive) is established. The ECMs of insulation materials were classified into walls, roofs, and floors. Also, economic evaluation databases, which are composed of material costs, labor costs, and expenses for constructed alternatives, were built. After setting the target building and deriving the ECM list of insulation materials for the target building, the energy use evaluation and economic evaluation were performed for each constructed alternative. Based on this, the optimal building energy conservation measure of the target building was derived by applying the decision-support process.